Supplementation with the Methyl Donor Betaine Prevents Congenital Defects Induced by Prenatal Alcohol Exposure. (11th October 2017) - Karunamuni, Ganga; Sheehan, Megan M.; Doughman, Yong Qiu; Gu, Shi; Sun, Jiayang; Li, Youjun; Strainic, James P.; Rollins, Andrew M.; Jenkins, Michael W.; Watanabe, Michiko
Abstract : Background: Despite decades of public education about dire consequences of prenatal alcohol exposure (PAE), drinking alcohol during pregnancy remains prevalent. As high as 40% of live‐born infants exposed to alcohol during gestation and diagnosed with fetal alcohol syndrome have congenital heart defects that can be life‐threatening. In animal models, the methyl donor betaine, found in foods such as wheat bran, quinoa, beets, and spinach, ameliorated neurobehavioral deficits associated with PAE, but effects on heart development are unknown. Methods: Previously, we modeled a binge drinking episode during the first trimester in avian embryos. Here, we investigated whether betaine could prevent adverse effects of alcohol on heart development. Embryos exposed to ethanol (EtOH) with and without an optimal dose of betaine (5 μ M) were analyzed at late developmental stages. Cardiac morphology parameters were rapidly analyzed and quantified using optical coherence tomography. DNA methylation at early stages was detected by immunofluorescent staining for 5‐methylcytosine in sections of embryos treated with EtOH or cotreated with betaine. Results: Compared to EtOH‐exposed embryos, betaine‐supplemented embryos had higher late‐stage survival rates and fewer gross head and body defects than seen after alcohol exposure alone. Betaine also reduced the incidence of late‐stage cardiac defects such as absent vessels, abnormal atrioventricular (AV) valves, and hypertrophic ventricles. Furthermore, betaine cotreatment brought measurements of great vessel diameters, interventricular septum thickness, and AV leaflet volumes in betaine‐supplemented embryos close to control values. Early‐stage 5‐methycytosine staining revealed that DNA methylation levels were reduced by EtOH exposure and normalized by co‐administration with betaine. Conclusions: This is the first study demonstrating efficacy of the methyl donor betaine in alleviating cardiac defects associated with PAE. These findings highlight the therapeutic potential of low‐concentration betaine doses in mitigating PAE‐induced birth defects and have implications for prenatal nutrition policies, especially for women who may not be responsive to folate supplementation. Abstract : Prenatal alcohol exposure causes heart defects. The quail embryo, that develops a four‐chambered heart, and Optical Coherence Tomography (OCT) were used to rapidly identify compounds that prevent ethanol‐induced abnormalities. OCT (A, B) allowed rapid analysis of heart defects including the great vessels of vehicle controls, ethanol‐exposed, and ethanol plus betaine cohorts. OCT obviated time‐consuming histological methods. While ethanol caused defects, including reduced great vessel diameters, the methyl donor betaine at a low concentration brought them back to normal (C).